Role of Ocean and Atmosphere Variability in Scale‐Dependent Thermodynamic Air‐Sea Interactions. Issue 7 (7th July 2022) - Laurindo, Lucas C.; Small, R. Justin; Thompson, LuAnne; Siqueira, Leo; Bryan, Frank O.; Chang, Ping; Danabasoglu, Gokhan; Kamenkovich, Igor V.; Kirtman, Ben P.; Wang, Hong; Zhang, Shaoqing
Abstract: This study investigates the influence of oceanic and atmospheric processes in extratropical thermodynamic air‐sea interactions resolved by satellite observations (OBS) and by two climate model simulations run with eddy‐resolving high‐resolution (HR) and eddy‐parameterized low‐resolution (LR) ocean components. Here, spectral methods are used to characterize the sea surface temperature (SST) and turbulent heat flux (THF) variability and co‐variability over scales between 50 and 10, 000 km and 60 days to 80 years in the Pacific Ocean. The relative roles of the ocean and atmosphere are interpreted using a stochastic upper‐ocean temperature evolution model forced by noise terms representing intrinsic variability in each medium, defined using climate model data to produce realistic rather than white spectral power density distributions. The analysis of all datasets shows that the atmosphere dominates the SST and THF variability over zonal wavelengths larger than ∼2, 000–2, 500 km. In HR and OBS, ocean processes dominate the variability of both quantities at scales smaller than the atmospheric first internal Rossby radius of deformation ( R 1, ∼600–2, 000 km) due to a substantial ocean forcing coinciding with a weaker atmospheric modulation of THF (and consequently of SST) than at larger scales. The ocean forcing also induces oscillations in SST and THF with periods ranging from intraseasonal to multidecadal, reflecting a red spectrum response to ocean forcing similar to that driven by atmospheric forcing. Such features are virtually absent in LR due to a weaker ocean forcing relative to HR. Plain Language Summary: This study investigates the importance of atmospheric processes (weather) and ocean currents in driving variations in sea surface temperature (SST) and the air‐sea heat exchange at mid‐latitudes. Our analysis uses satellite observations, a high‐resolution (HR) climate model that resolves ocean currents with dimensions of tens of km, and a low‐resolution model (LR) that can only simulate ocean currents with hundreds of km in size. We specifically examine the SST and heat exchange variability resolved by these datasets at horizontal scales between 50 and 10, 000 km and time scales from 2 months to 80 years in the Pacific Ocean. Using a simple mathematical model to interpret the results, we find that variability at scales larger than 2, 000 km is driven predominantly by weather. At smaller scales, SST and heat exchange are more variable in HR than in LR and agree better with satellite observations. We also find that ocean processes drive variability in SST with time scales ranging from 2 months to several decades, similar to those caused by weather, which in turn induces slow variations in the air‐sea heat exchange. Key Points: We use spectral methods to examine the role of oceanic and atmospheric processes in Pacific sea surface temperature (SST) and turbulent heat flux variability At mid‐latitudes, the atmosphere controls variability with scales larger than 2, 000 km while ocean processes dominate at smaller scales Ocean phenomena drive a red spectrum SST response similar to that induced by the atmosphere, which is mirrored by the turbulent fluxes